MANAJEMEN INFORMASI DAN SISTEM BASIS DATA DALAM PENGELOLAAN PENDIDIKAN ISLAM - Yeni Amalia; Dina Hermina (PT. Saha Kreasi Indonesia, 2026)
Digital transformation requires Islamic educational institutions to manage information in a systematic, integrated, and data-driven manner. This article aims to conceptually analyze the role of information management and database systems in enhancing the effectiveness of Islamic education management from an Islamic perspective. This study employs a literature review method by examining relevant books, scholarly journals, and academic sources. The findings indicate that the implementation of Management Information Systems and database systems significantly improves administrative efficiency, supports data-driven decision-making, and strengthens accountability and transparency in Islamic educational institutions. The integration of Islamic values such as trustworthiness (amanah), justice, responsibility, and tawhid provides an ethical foundation for managing educational information, positioning information technology as a means to achieve the objectives of Islamic education. Therefore, the development of information management based on Islamic values is a strategic necessity to enhance the quality and competitiveness of Islamic educational institutions in the digital era.